From Waste to Water - An Integrated System to Recover Potable Water from Urine and Condensate - Helgeland, Ingrid; Vogel, Jörg; Tommerup, Maja Bender; Ogden, Jason A. (2023 International Conference on Environmental Systems, 2023)
Ingrid Helgeland, Aquaporin A/S, Denmark Jörg Vogel, Aquaporin A/S, Denmark Maja Bender Tommerup, Danish Aerospace Company, Denmark Jason A. Ogden, Danish Aerospace Company, Denmark ICES303: Physio-Chemical Life Support- Water Recovery & Management Systems- Technology and Process Development The 52nd International Conference on Environmental Systems was held in Calgary, Canada, on 16 July 2023 through 20 July 2023. The Water Recovery Unit (WRU) is based on an open loop triple circulation system with two-stage filtration and the start of its development has been reported at ICES 2018 and 2019. Here, we identified several challenges. The first stage, based on forward osmosis (FO),separating water from the contaminated urine/condensate mix, suffered from precipitation and storage challenges which lead to lower water recovery and reduced system lifetime. The second stage was designed as a vacuum assisted membrane distillation (MD) process and was challenged by low water flux and shorter than required membrane lifetime. Throughout the past years we worked on an improved design and integrated several upgrades to both stages.This includes a concept for better waste storage, improved water recovery and improved water recovery sub-system that will enable us to produce water in sufficient quantity and quality. Despite the improvements to the complete system all components are still designed to be lightweight and easy to operate with the only external connection to the unit to be power and the supply of contaminated water.